The effect of paraquat dichloride and carbosulfan on soil conditions and population dynamic of soil microbes in a cornfield: a case study in Sumedang, West Java - Taufikurahman, Taufik; Aryantha, I Nyoman P; Purwasena, Isty Adhitya; Zahra, Muhandinni; Stefania, Marchia; Fitriyani, Azizah Nur Fitriyani (Institut Teknologi Bandung, 2024)
Paraquat dichloride (PC) is one of the herbicides active ingredients that is widely used by farmers to control various types of weeds, while carbosulfan (CS) is one of the insecticide’s active ingredients that is widely used to control various types of insect pests. The objective of this study is to analyze the impact of pesticides for PC and CS on the chemical and physical conditions of the soil and the dynamics of fungi and soil bacteria population in a corn field in Sumedang district, West Java. The experiment took place between August and October, during the dry season, concluding just as the rainy season began. The PC concentrations used were 0 mL/L, 3.33 mL/L, 4 mL/L, 4.66 mL/L and 5.33 mL/L, while the CS concentrations used were 0 mL/L, 0.5 mL/L, 1 mL/L, 1.5 mL/L and 2 mL/L. Soil sampling was conducted before and after the application of pesticides. The total abundance of fungi and bacteria was analyzed using the total plate count (TPC) method. The application of PC to the cornfield slightly decreased soil bulk density from 1.354 g/cm3 to 0.816 g/cm3, while the application of CS slightly increased soil bulk density. A decrease in bulk density is considered positive for the physical conditions of the soil for plant cultivation. In general, the result indicated that the application of PC and CS did not show a significant effect on the chemical characteristics of the soil, and also it did not affect the population of fungi and bacteria. Weather conditions, i.e. dry season (June-September) and rainy season (started from October) seem to affect more on soil conditions as well soil microbial population than the application of the pesticides.